SISTEM PANASBUMI BERDASARKAN ANALISIS GEOKIMIA AIR PANAS DAERAH AMOHOLA DAN SUMBERSARI, KECAMATAN MORAMO, KABUPATEN KONAWE SELATAN, PROVINSI SULAWESI TENGGARA - Aprilia, Fitriani Dewi; Yuningsih, Euis Tintin; Patonah, Aton; Rezky, Yuano; Yushantarti, Anna; Nurdin, Asep (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
The research area is located in Amohola and Sumbersari, Moramo sub-district, Konawe South regency, Southeast Sulawesi Province. Geographically located between 122°35’6,07